Evaluating the chemical and rheological attributes of aged asphalt: synergistic effects of maltene and waste engine oil rejuvenators - Putra Jaya, Ramadhansyah; Zaid Hazim, Al-Saffar; Haryati, Yaacob; Mohd Khairul Idham, Mohd Satar; Saleem, Mhmood Khleel; Choy, Jau Lai; Ekarizan, Shaffie (Springer, 2020)
The service life of road pavement reduces as it ages and loses its properties due to the exposure to varying traffic loads and climatic conditions. This study explores the potential rejuvenation of the aged asphalt properties to enable it to be reused in pavement by adding hybrid rejuvenator (WEO-MLT). The WEO-MLT is composed of waste engine oil and maltene (MLT). Four types of binders, namely virgin asphalt, aged asphalt, 40% aged asphalt and rejuvenated asphalt, were prepared and evaluated via rheological and chemical tests [e.g. storage stability, asphaltene-to-MLT ratio, dynamic shear rheometer, bending beam rheometer, Fourier transform infrared (FTIR), thermogravimetric analysis and stripping resistance tests]. The results revealed that the WEO-MLT markedly enhanced the properties of aged asphalt at low and high temperatures. In contrast, the outcomes of FTIR suggested that the ageing properties of asphalt were not improved significantly by WEO-MLT due to the presence of a carboxyl group in its composition. TGA indicated that the initial decomposition for rejuvenated asphalt was approximately close to virgin asphalt. The stripping resistance test divulged the comparable performance of the rejuvenated asphalt to that of virgin asphalt. Therefore, WEO-MLT can be potentially used in the rejuvenation of the aged asphalt, paving the way to sustainable and eco-friendly asphalt production.